Creating a quiet buzz: opportunities and challenges for meaningful participation of boreal forest apiarists in the science-policy interface for biodiversity and ecosystem services - Agnieszka Pawłowska-Mainville (Ecology and Society)
Boreal apiary and beekeeping are characteristic of Eastern Europe and are passed down from generation to generation. Boreal apiary relies on ecological and cultural knowledge to protect honeybee diversity, change forestry practices, and ensure sustainable livelihoods. In this article I discuss the participation of Polish apiarists in the science-policy interface for biodiversity and ecosystem services IPBES Values Assessment and the Indigenous and Local Knowledge (ILK) meetings. Although the process permitted recognition of boreal apiary at a global stage, several obstacles, including essentialist typologies and Anglophone scientific discourses, convoluted meaningful participation. By elaborating on the apiarists’ ecocultural knowledge, I summarize the IPBES ILK Process, the limitations of active engagement by the apiarists, and offer considerations to make science-policy interface ILK engagement more inclusive for culture-custodians.